Transdermal estrogen gel and oral aspirin combination therapy improves fertility prognosis via the promotion of endometrial receptivity in moderate to severe intrauterine adhesion - Chi, Yugang (Mol Med Rep, 2018)
Intrauterine adhesion (IUA) is one of the most common gynecological diseases in women of reproductive age. IUA, particularlyin moderate to severe forms, accounts for a large percentage of infertility cases. Clinically, the first-line treatment strategy for IUA is transcervical resection of adhesion (TCRA), followed by adjuvant postoperative treatment. Estrogen is one of the classic chemotherapies used following TCRA and contributes to preventing re-adhesion following surgery. However, estrogen has limited effects in promoting pregnancy, which is the ultimate goal for IUA management. In the present study, a transdermal estrogen gel and oral aspirin combination therapy was used in patients with IUA following TCRA. Compared with in the control group (transdermal estrogen only therapy), the combination therapy significantly increased endometrial receptivity marker (αvβ٣ and laminin) expression in endometrium tissues. Additionally, ultrasonic examination revealed the pulsatility index and resistant index of the uterine artery were lower in the combination therapy group. Combination therapy promoted angiogenesis and prevented fibrosis following TCRA more effectively than estrogen-only therapy. Collectively, the evaluation indices, including American Fertility Society score, endometrial parameters and pregnancy rate, indicated that patients with combination therapy had better prognoses in endometrial repair and pregnancy. In conclusion, postoperative combination therapy with transdermal estrogen gel and oral aspirin may be more efficacious in enhancing endometrial receptivity by increasing uterine blood and angiogenesis, contributing to improved fertility prognosis. The findings of the present study may provide novel guidance to the clinical treatment of IUA.